Colonic Adenocarcinoma Presenting as Splenic Abscess Secondary to Suspected Microperforation - Emily Fitzsimmons BS; Tyler J. Torrico MD; Tushar Bajaj MD; Alan Scott Ragland DO (SAGE Publishing, 2020)
Splenic abscesses are a rare infection that usually requires seeding from another primary source; however, direct contact of bacteria can occur with microperforation secondary to colon cancer leading to abscess formation. This occurrence is rare, and through literature review only 12 previous cases have been reported with associated bacteremia. Our patient is a 62-year-old female who presented with left upper quadrant pain with a history of tobacco and alcohol abuse that was febrile and hypoxic. Blood cultures were obtained that eventually grew Fusobacterium mortiferum . Computed tomography of the abdomen and the pelvis revealed 2 splenic abscesses that were cultured to grow Escherichia coli and β-hemolytic Streptococcus group C. Colonoscopy was performed, which identified 2 masses that were biopsied, and histopathology confirmed well-differentiated adenocarcinoma with possible muscular invasion. The patient had no other identifiable risk factors for bacterial seeding from another primary source. We present the first reported case report of splenic abscess secondary to colonic adenocarcinoma suspected microperforation associated with Fusobacterium mortiferum bacteremia.